2002
DOI: 10.1093/gerona/57.8.m511
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Based Therapeutic Approaches in Treatment of Anorexia of Aging and Cancer Cachexia

Abstract: Loss of appetite, or anorexia, has profound implications for older persons, altering social interactions, reducing quality of life, and leading to weight loss with grave health consequences. Two conditions associated with anorexia considered in this article are the multidetermined anorexia of aging and the wasting syndrome termed cachexia induced by cancer. Nutritional interventions may have some benefit in the former, but are of limited value in the latter. Emerging studies at the molecular level relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 127 publications
0
22
0
Order By: Relevance
“…Evidence from laboratory and clinical studies has demonstrated that EPA has antitumor and anticachectic effects. Initial studies using animal models have demonstrated that NFkB is upregulated in CC increasing proteolysis and inducing apoptosis in myotubes [43, 44]. Several recent laboratory studies have shown that EPA may attenuate protein degradation, by preventing NFkB accumulation in the nucleus [43, 44].…”
Section: Treatmentmentioning
confidence: 99%
“…Evidence from laboratory and clinical studies has demonstrated that EPA has antitumor and anticachectic effects. Initial studies using animal models have demonstrated that NFkB is upregulated in CC increasing proteolysis and inducing apoptosis in myotubes [43, 44]. Several recent laboratory studies have shown that EPA may attenuate protein degradation, by preventing NFkB accumulation in the nucleus [43, 44].…”
Section: Treatmentmentioning
confidence: 99%
“…One of the systems that is particularly affected with aging is that which regulates food intake and energy balance, leading to a decreased ability to maintain body weight and lean body mass in response to illness or disease (15,16,20,23,34,36,46,47). One of the key factors appears to be failure of appetite to increase after weight loss (7,36,48,49).…”
mentioning
confidence: 99%
“…In addition, older people report less hunger after an overnight fast and report greater degrees of satiation to meals than do younger subjects (7,49). This apparent insensitivity to metabolic cues can lead to inappropriate weight loss in response to acute or chronic illness or other stressors, including surgery, resulting in greater morbidity and mortality associated with frailty in geriatric populations (15,20,36).…”
mentioning
confidence: 99%
“…In addition, older people report less hunger after an overnight fast and report greater degrees of satiation to meals than do younger subjects (8,44,56). This apparent insensitivity to metabolic cues can lead to inappropriate weight loss in response to acute or chronic illness or other stressors, resulting in greater morbidity and mortality in geriatric populations (19,25,38).Our laboratory uses the Brown Norway (BN) rat to study aging-related decrements in reproductive function and regulation of body weight (22,36). Male BN rats are an excellent model for human aging: they have long disease-free survival rates (52) and a maximum life span of ϳ36 mo, with 50% surviving to 30 mo (comparable to 80 yr of age in humans), and 10% surviving to 32 mo of age (52).…”
mentioning
confidence: 99%
“…In addition, older people report less hunger after an overnight fast and report greater degrees of satiation to meals than do younger subjects (8,44,56). This apparent insensitivity to metabolic cues can lead to inappropriate weight loss in response to acute or chronic illness or other stressors, resulting in greater morbidity and mortality in geriatric populations (19,25,38).…”
mentioning
confidence: 99%